Surface electromyographic biofeedback versus neuromuscular electrical stimulation for post-stroke dysphagia: a systematic review and network meta-analysis - Li, Na; Jin, Qianqian; Zhang, Yi; Zhang, Li; Peng, Xiapei (Frontiers in Neurology, 2025)
BackgroundPost-stroke dysphagia (PSD) is a common complication with a high incidence rate, significantly impairing patients’ quality of life and health. Although conventional swallowing training is widely used, its efficacy depends on interindividual heterogeneity. Surface electromyographic biofeedback (sEMG-BF) is an emerging rehabilitation technology that shows promising potential in improving swallowing function. However, there is a lack of systematic and comprehensive evaluation and high-quality evidence to support its clinical application.ObjectiveThis study aims to systematically evaluate and conduct a network meta-analysis comparing the efficacy of sEMG-BF, NMES, and conventional therapy in improving electrophysiological outcomes, swallowing function, and quality of life for patients with PSD.MethodsA systematic review and network meta-analysis were conducted by searching databases, including PubMed, EMBASE, Cochrane Library, Web of Science, and Scopus for prospective randomized controlled trials on the application of sEMG-BF in patients with PSD. We included randomized controlled trials that compared sEMG-BF, NMES, or conventional therapy in patients with PSD. The study focused on the effects of sEMG-BF on electrophysiological outcomes in these patients.ResultsSix studies were included in the analysis. sEMG-BF was found to significantly increase mean amplitude (MD = 6.45, 95% CI: 3.53, 9.38) and reduce swallowing duration (MD = −0.22, 95% CI: −0.26, −0.18). The network meta-analysis revealed the following SUCRA ranking: sEMG-BF, neuromuscular electrical stimulation (NMES), and conventional therapy. sEMG-BF significantly improved the Standardized Swallowing Assessment (SSA) score (MD = −6.43, 95% CI: −9.74, −3.11). For Swallowing Quality of Life (SWAL-QOL), the pooled estimate was MD = 29.36 (95% CI: −14.96, 73.69), which did not reach statistical significance. The network meta-analysis demonstrated that sEMG-BF outperformed NMES and conventional therapy in improving swallowing function, consistent with direct comparison results.ConclusionThis study suggests that both sEMG-BF and NMES may provide benefits for PSD. Although sEMG-BF demonstrated superior effects in the majority of outcomes, the evidence is limited by small sample sizes and heterogeneity. Further high-quality trials are needed to confirm its efficacy. By enhancing the amplitude of electromyographic signals in swallowing-related muscles and improving muscle contraction capacity, sEMG-BF improves swallowing function; however, the pooled SWAL-QOL estimate was not statistically significant.